The Role of Teachers in Cultivating Good Manners & Halal Food Through Mother’s Previsions - Nur Inten, Dinar; Mulyani, Dewi; Aziz, Helmi (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Early childhood children are unique individuals and are equipped with millions of potentials. This potential will grow and develop optimally if it gets good and correct stimulus. One of them is introducing Rasulullah's eating habits and getting children used to consuming halal and thoyyib food. Teachers are one of the important figures in children's learning. From teachers, children learn a variety of information, knowledge and skills. The aim of this research is to determine children's understanding and skills in eating and consuming halal and thoyyib food through mother's provisions. The method used was quasi-experimental with research objects of children aged 5-6 years. The results of the research prove that through eating activities carried out with correct etiquette, children get used to eating in a civilized way. Likewise, mother's provisions make children accustomed to consuming halal and thoyyib food in their daily lives.